Plan de negocio para la construcción de un complejo turístico ecológico en Mindo-Ecuador - Ortiz Delgado, Jorge Armando (2012)
Considering that tourism has been declared by the Ecuadorian State an Strategic Sector, recorded the growth rates are higher than the national economy ones and new trends in the industry point to products as eco-tourism and tourism of adventure, these variables have to be consider to promote a new project investment in the Industry. After making a thorough field study, gathering information and statistics from Public Institutions such as Superintendencia de Compañías, Ministerio de Turismo, Instituto Nacional de Estadísticas y Censos and Banco Central del Ecuador, and also consulting works of renowned authors, was obtained some valuable information that formed the basis for a technical and economic study; which presents favorable results for the creation of an eco-lodge. The purpose of this business plan is to demonstrate the positive social and economic impact that will generate in the town of Mindo, determine the market share obtained, the initial investment required, an appropriate organizational structure and to obtain profitable margins for the company. Designing a full business model based on the knowledge acquired in university.